Beberapa Perspektif Feminis dalam Menganalisis Permasalahan Wanita - Siti Hidayati Amal (Antropologi Indonesia, 1992)
This article presents some of the feminist perspectives written by Rosemarie Tong (1989). Each of these perspectives has its own basic assumption in analyzing women's issue. Based on their analysis of causes and consequences of women's backwardness, it prescribes strategies for women's progress. However, each of these perspectives only give a partial and provisional answer to women's issues providing a unique perspective with its own methodological strengths and weakness.